Effect of Inspiratory Muscle Training on Pulmonary Function in Multiple Sclerosis Patient - Mohamed El-Nozahay, Faten Mohamed; Mashaal, Ahmed Hussein; Mahmoud, Hend Mohamed; Ahmed, Mona Sayed; El-Din, Mohamed Y. Gamal; Gad Allah, Mohamed Ahmed; Ahmed Zaid, Alyaa Abdallah Atallah (Journal of Neonatal Surgery, 2025)
Background: Multiple sclerosis (MS) is a primary, chronic inflammatory, and progressive disease caused by the demyelinated of the central never system that may affected motor pathway and cause muscle weakness, respiratory muscles also affected, MS is one of the most common disease of CNS in younger adult with incidence of 30-110 per 100,000 adults worldwide and affecting approximately 2.5 million people worldwide. Weakness of the respiratory muscles can result in impaired coughing efficacy, potentially leading to aspiration pneumonia or abrupt ventilatory failure, conditions that often result in mortality in multiple sclerosis. Training the respiratory muscles may enhance respiratory function and cough effectiveness. Objectives: To Investigate the effects of inspiratory muscle training (IMT) on pulmonary function in MS patients. Methods: The neurology department of Minia University Hospital selected a sample of 40 MS patients, aged 25-45, from both genders (26 women and 14 men). The patients were randomly assigned to two groups, each of which received 24 sessions, three times per week, for a period of eight weeks. In addition to conventional chest physiotherapy, twenty patients with multiple sclerosis in Group A received inspiratory muscle training using an IMT device. Twenty patients in Group B received conventional chest physiotherapy exclusively. Before and after treatment, both groups underwent assessments of their pulmonary functions (Plmax, FVC, FEV1, MVV, PEFs). Results: The pulmonary functions (FVC, FEV1, Plmax, MVV, PEF) in group (A) increased by 22.74%, 27.72%, 39.20%, 33.34%, and 35%, respectively, following the treatment regimen. In group (B), the P lmax increased by 17.52%. Conclusion: The primary choice in the rehabilitation program of multiple sclerosis patients should be Inspiratory Muscle Training (IMT), as it has been shown to significantly enhance pulmonary functions by increasing the strength of the respiratory muscle.